Carbon-storage capacity of seagrasses at Lang Co Lagoon, Thua Thien Hue province - Nguyễn, Tú Uyên; Trần Ngọc, Khánh Ni; Ngô, Hữu Bình; Nguyễn, Hữu Chí Tư; Hoàng, Thị Bình Minh; Mai, Anh Thư; Zschiesche, Michael; Hoàng, Công Tín (Hue University Journal of Science: Natural Science, 2023)
Seagrass beds play an essential role in mitigating climate change by absorbing CO2 from the atmosphere and converting carbon into biomass through photosynthesis. We used remote sensing and GIS technology with field survey data to establish the distribution and above-ground dry biomass maps of seagrass beds in 2021. A Landsat 8 OLI satellite image was used in the interpretation process. An above-ground dry biomass map was established by building the regression function between the above-ground dry biomass and the reflectance spectrum of the image bands. The overall accuracy and the Kappa coefficient of the classification process were 95.5% and 0.94. At Lang Co Lagoon, the seagrass bed area in 2021 was about 36.18 ha, distributed primarily in the area between Lang Co Town and the north of the lagoon; and scattered in the north of the lagoon, Hoi Can, Hoi Dua, and Hoi Mit. In addition, the total carbon stock of seagrasses in Lang Co Lagoon was estimated at 5.54 tons, equivalent to 20.32 tons of CO2, in which the contribution of Halodule uninervis accounted for 61% of the total carbon stock.